Assessment of likelihood of cocrystal racemic ibuprofen/alpha-lactose monohydrate formation: experimental and molecular modelling / Mohd Zulfahmi Lukman - Lukman, Mohd Zulfahmi (2015)
Crystallization from solution and melt is increasingly important method for separation and purification process in wide varieties of industries such as pharmaceutical industry. Pharmaceutical crystallization specifically involves drugs of a high degree of chemical complexity. To date, sugar based-drug cocrystal produced either in melt or solution involving alpha-lactose monohydrate is yet to be reported. Thus, possibility of formation of alpha-lactose monohydrate-racemic ibuprofen cocrystal either in solution or melt is not known. This study is conducted to analyze the formation of product crystals recovered from PEG 300 solutions containing alpha-lactose monohydrate, racemic ibuprofen; and the possibility of cocrystal formation of product crystals from alpha-lactose monohydrate/racemic ibuprofen system in solution via polyethylene glycol 300 aqueous solution and in melt via physical mixtures. The objective of this thesis to determine the solid state properties and possible formation of cocrystals on product crystals grown via trial and error method, melted physical mixtures and melted granules. Possible crystal morphology and formation of cocrystal is simulated using molecular modelling.The morphological prediction in vacuum using suitable force fields and hence surface chemistry of alpha-lactose monohydrate and racemic ibuprofen was carried out first as preparation for cocrystal prediction. The cocrystal prediction or binding between alpha-lactose monohydrate and racemic ibuprofen was checked on its availability of mutual formation of hydrogen bond. The predicted lattice energy of alpha-lactose monohydrate and racemic ibuprofen was in agreement with the experimental lattice energy with percentage errors of 3.9 % and 0.02%, respectively. The morphology of alpha-lactose monohydrate is predicted to be elongated hexagonal, similarly found when alpha-lactose monohydrate was grown in PEG 300 solutions. However, the predicted morphology of racemic ibuprofen contradicted with the experimental ones. It was found that the lattice energy of alphalactose monohydrate was dominated by the weak van der Waals force, so did racemic ibuprofen. All alpha-lactose monohydrate surfaces or facets were tested by modelling the binding of racemic ibuprofen onto the surfaces. Successful binding prediction of five facets by surface docking method proved that racemic ibuprofen was capable to attach to certain facets of alpha-lactose monohydrate. This occurred by alpha-lactose monohydrate layers accepting hydrogen and oxygen atoms of racemic ibuprofen, thus forming co-crystal. Results of powder FTIR, DSC and XRD on melted granules, melted physical mixtures and crystals grown from PEG 300 solutions containing racemic ibuprofen and alpha-lactose monohydrate, respectively indicated that the substance was not co-crystal within this scope of experimental study.